Rules Regarding Mandatory Equity Securities Listing: Is It Possible for A Public Company Without Listing on The Indonesian Stock Exchange? - Ayup Suran Ningsih (Jurnal Penelitian Hukum De Jure, 2022)
ABSTRACTThe Financial Services Authority has issued the latest regulation in the Capital Market sector, namely the Financial Services Authority Regulation Number 3/POJK.04/2021 concerning the Implementation of Activities in the Capital Market Sector. This paper aims to conduct a more specific analysis regarding the mandatory elements for a company that will conduct a public offering to list its equity securities on the stock exchange. The initiation of the obligation to conduct equity securities listing is carried out in order to reduce the intensity of backdoor listing or efficient efforts towards Initial Public Offering activities by acquiring a company whose shares have been listed on the Stock Exchange. This article was compiled using a normative legal research method. Based on Financial Services Authority Regulation Number 3/POJK.04/2021, the Financial Services Authority through the Depository and Settlement Institution conducts electronic securities listing which is not part of the securities collective custody. The Depository and Settlement Institution checks the conformity of the Securities records in the Depository and Settlement Institution with the records in the Securities Administration Bureau or the Public Company which conducts its own Securities administration. The mandatory to be listed for the equity securities of a public company closes legal loopholes for companies that wish to become public company using a procedure that is not in accordance with the provisions of the prevailing laws and regulations.Keywords: registered; capital market; public company; securities